PENGARUH MODAL KERJA, LIKUIDITAS DAN RETURN ON ASSETS (ROA) TERHADAP KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - Okta vianti; Shella Kurnia (EQUILIBIRIA, 2018)
This research aims to provide empirical evidence for the company and investors in the form of information that is important to know the influence of the Working Capital, Liquidity and Return On Assets (ROA)against the Financial Performance. This research is a quantitative type because in it refers to the calculation of research data in the form of numbers. The variables of this study include dependent and independent variables. The sample in this research is Construction and Buildingthat listed in Indonesia Stock Exchange (BEI) period 2013-2016. The sample was chosen using purposive sampling method, with the number of 9 (nine) companies during the period 2013-2016. Data analysis techniques use classical assumption test, multiple linear regression analysis and hypothesis test. This analysis is done by using SPSS 20 program. This research shows that the variable of Working Capital and Liquiditypartially have no significant effect to Financial Performance and variable Return On Assets (ROA) have significant effect toFinancial Performancewhile simultaneously have low effect to Financial Performance.